Ultrathin aramid paper flame-retardant adhesive tape and preparation method thereof
By using thin-layer structure and composite flame retardant in aramid paper flame retardant tape, the problems of degradation of mechanical properties and insufficient flame retardant performance during ultra-thinization are solved, and efficient flame retardant and mechanical properties are achieved, which is suitable for precision electronic equipment.
Patent Information
- Application Number
- CN202510078149.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-11
AI Technical Summary
The existing aramid paper flame retardant tape has problems such as degradation of mechanical properties and insufficient flame retardant properties during ultra-thinization, especially in precision electronic equipment.
The aramid paper substrate with a thickness of 0.03-0.06 mm, a flame retardant adhesive layer with a thickness of 0.02-0.03 mm, and a release layer with a thickness of 0.005-0.01 mm were used. The flame retardant adhesive layer consisted of 40-55 parts of a single component polyurethane adhesive, 10-15 parts of silicone and 3-7 parts of a composite flame retardant, and the composite flame retardant includes phenylsilane microspheres, zinc borate and modified graphene oxide.
It realizes the good flexibility of ultra-thin aramid paper flame retardant tape, improves its mechanical properties and flame retardant properties, making it suitable for fine operation and high temperature environments.
Abstract
Description
Technical Field
[0001] The present application relates to the field of flame retardant tapes, and more specifically, to an ultra-thin aramid paper flame retardant tape and a preparation method thereof. Background Art
[0002] Aramid paper tape is a high-performance tape with aramid paper as the base material. It has excellent high temperature resistance, fire retardancy and electrical insulation properties. Aramid paper tape is widely used in the insulation wrapping protection of the ends of new energy power batteries and lithium-ion batteries, the protection and fixation of electronic and electrical products such as motors, electrical machinery, and high-temperature insulation protection of transformers and electrical coils. Due to its excellent high temperature resistance and electrical insulation properties, aramid paper tape plays an important role in the electrical industry.
[0003] However, with the continuous improvement of requirements, the existing aramid paper flame retardant tapes generally have problems such as thick thickness, insufficient flexibility, and limited high temperature resistance. Traditional flame retardants, such as organophosphorus, bromides, metal hydroxides, etc., have poor compatibility with aramid fibers, resulting in a decrease in the mechanical properties of the flame retardant tape. This problem is more prominent, especially in the ultra-thin process, which seriously restricts its widespread application in precision electronic equipment. Summary of the invention
[0004] In order to ensure the mechanical properties and flame retardant properties of an ultra-thin aramid paper tape, the present application provides an ultra-thin aramid paper flame retardant tape and a preparation method thereof.
[0005] In a first aspect, the present application provides an ultra-thin aramid paper flame retardant tape, which adopts the following technical solution: An ultra-thin aramid paper flame-retardant tape, comprising an aramid paper substrate with a thickness of 0.03-0.06 mm, a flame-retardant adhesive layer with a thickness of 0.02-0.03 mm, and a release layer with a thickness of 0.005-0.01 mm; The flame retardant adhesive layer comprises the following raw materials in parts by weight: 40-55 parts of a single-component polyurethane adhesive, 10-15 parts of siloxane and 3-7 parts of a composite flame retardant; the release layer is formed by coating a release liquid and drying it.
[0006] By adopting the above technical scheme, the thickness of the aramid paper substrate is relatively thin, the aramid paper has good high temperature resistance, fire retardant and electrical insulation properties, the single-component polyurethane adhesive has high-strength adhesion, and the polyurethane has relatively good flexibility. The flame retardant adhesive layer and the aramid paper substrate are compounded to effectively provide the flexibility of the ultra-thin aramid paper flame retardant tape. The composite of siloxane and the single-component polyurethane adhesive can effectively improve its mechanical properties and flame retardant properties, and improve the bonding force of the flame retardant adhesive layer. The addition of the composite flame retardant can further provide the flame retardant properties of the flame retardant adhesive layer.
[0007] Preferably, the composite flame retardant comprises phenylsilane microspheres, zinc borate and modified graphene oxide.
[0008] By adopting the above technical scheme, the addition of phenylsilane microspheres can increase the residual carbon content of the polyurethane adhesive layer, which is beneficial to the stability of the carbon layer. At the same time, the phenylsilane microspheres help to form more carbon layers at high temperatures, reduce the combustion rate and heat release rate of the material, thereby improving the thermal stability of the material, and modifying the good insulation and flame retardant properties of graphene oxide. At the same time, the modified graphene oxide can form a dense carbon layer and improve the thermal stability of the material.
[0009] Preferably, the mass ratio of phenylsilane microspheres, zinc borate and modified graphene oxide in the composite flame retardant is (1.25-1.67):(0.68-0.89):(0.98-1.32).
[0010] By adopting the above technical scheme, there is a synergistic effect between phenylsilane microspheres, zinc borate and modified graphene oxide, which can synergistically improve the flame retardant properties of the single-component polyurethane adhesive, thereby effectively improving the flame retardant properties of the ultra-thin aramid paper flame retardant tape.
[0011] Preferably, the preparation method of the phenylsilane microspheres comprises the following steps: adding an emulsifier to a sodium hydroxide solution, heating to 45-50°C, stirring evenly, dripping phenyltrimethoxysilane, reacting for 2-2.3 hours, adding 10wt% acetic acid to neutralize to a pH of 7, filtering, washing with water, washing with methanol, and drying at 100-105°C for 2-2.2 hours to obtain phenylsilane microspheres.
[0012] By adopting the above technical scheme, phenyltrimethoxysilane is hydrolyzed and polymerized in an alkaline solution to form phenylsilane microspheres. The microspheres have a regular shape and there is no adhesion between the microspheres, so that the phenylsilane microspheres are evenly dispersed in the single-component polyurethane adhesive, thereby improving the flame retardant properties of the flame retardant adhesive layer, and further improving the flame retardant properties of the ultra-thin aramid paper flame retardant tape.
[0013] Preferably, the phenylsilane microspheres are further treated as follows: the phenylsilane microspheres are added to an alcohol aqueous solution of magnesium chloride, a dispersant is added, and after ultrasonic dispersion is uniformly performed, an alcohol aqueous solution of sodium hydroxide is dripped into the microspheres at 55-60° C., reacted for 18-19 hours, washed alternately with water and ethanol until the pH is 7, and dried at 100-110° C. for 5-6 hours.
[0014] By adopting the above technical scheme, magnesium chloride and sodium hydroxide form magnesium hydroxide, and the magnesium hydroxide is deposited and adsorbed on the surface of the phenylsilane microspheres, so that the surface of the phenylsilane microspheres is coated with a layer of magnesium hydroxide. Under high temperature, the magnesium oxide produced by the decomposition of magnesium hydroxide can block heat transfer and radiation, and play a role in isolating heat sources and air, thereby further improving the flame retardant properties of the phenylsilane microspheres.
[0015] Preferably, the preparation method of the modified graphene oxide comprises the following steps: ultrasonically dispersing graphene oxide in a mixed solution of ethanol and water, adding 10wt% ammonia solution and stirring evenly, adding tetraethoxysilane, stirring for 24h, vacuum filtering, ethanol washing, suction filtering, and vacuum drying.
[0016] By adopting the above technical scheme, after the graphene oxide is ultrasonically dispersed, tetraethoxysilane is hydrolyzed to form silicon dioxide which is deposited on the surface of the graphene oxide. The silicon dioxide has good flame retardant and insulating properties and can further improve the insulating properties of the flame retardant adhesive layer and the ultra-thin aramid paper flame retardant tape.
[0017] Preferably, the modified graphene oxide is further treated as follows: ultrasonically dispersing the modified graphene oxide in Tris-HCl buffer, adding dopamine hydrochloride, magnetically stirring at room temperature for 24 hours, centrifuging, washing with ethanol, and drying.
[0018] By adopting the above technical scheme, after the modified graphene oxide is treated, dopamine self-polymerizes on the surface of the modified graphene oxide to form a polydopamine layer, which can effectively improve the dispersibility of the modified graphene oxide, so that the modified graphene oxide can be evenly dispersed in the single-component polyurethane adhesive, thereby effectively improving the flame retardant effect of the flame retardant adhesive layer.
[0019] In a second aspect, the present application provides a method for preparing an ultra-thin aramid paper flame retardant tape, using the following technical solution: A method for preparing an ultra-thin aramid paper flame-retardant tape comprises the following steps: A release liquid is coated on one side of an aramid paper substrate, and a release layer is formed after heating and drying; a single-component polyurethane adhesive, siloxane and a composite flame retardant are stirred and mixed, and coated on the side of the aramid paper substrate away from the release layer, and a flame retardant adhesive layer is formed after hot pressing and curing, and the layer is rolled up to obtain an ultra-thin aramid paper flame retardant tape.
[0020] By adopting the above technical solution, an ultra-thin aramid paper flame-retardant tape with good flame-retardant properties can be formed, and the bonding effect of the flame-retardant adhesive layer is relatively good, and it is suitable for delicate operations.
[0021] In summary, this application has the following beneficial effects: 1. In the present application, the thickness of the aramid paper substrate is relatively thin, the aramid paper has good high temperature resistance, fire retardant and electrical insulation properties, the single-component polyurethane adhesive has high-strength adhesion, and the polyurethane has relatively good flexibility. The flame retardant adhesive layer and the aramid paper substrate are compounded to effectively provide the flexibility of the ultra-thin aramid paper flame retardant tape. The composite of siloxane and the single-component polyurethane adhesive can effectively improve its mechanical properties and flame retardant properties, and improve the bonding force of the flame retardant adhesive layer. The addition of the composite flame retardant can further provide the flame retardant properties of the flame retardant adhesive layer.
[0022] 2. Phenylsilane microspheres are used in this application. The addition of phenylsilane microspheres can increase the residual carbon content of the polyurethane adhesive layer, which is beneficial to the stability of the carbon layer. At the same time, phenylsilane microspheres help to form more carbon layers at high temperatures, reduce the combustion rate and heat release rate of the material, and thus improve the thermal stability of the material.
[0023] 3. In the present application, after the graphene oxide is ultrasonically dispersed, tetraethoxysilane is hydrolyzed to form silicon dioxide which is deposited on the surface of the graphene oxide. Silicon dioxide has good flame retardant and insulating properties, and can further improve the insulating properties of the flame retardant adhesive layer and the ultra-thin aramid paper flame retardant tape. DETAILED DESCRIPTION
[0024] The present application is further described in detail below with reference to the embodiments. Preparation Example 1-7 of Phenylsilane Microspheres
[0025] Preparation Example 1 The preparation method of phenylsilane microspheres comprises the following steps: adding emulsifier OP-10 to a sodium hydroxide solution, heating to 48°C, stirring evenly, dripping phenyltrimethoxysilane at 3 g / min, reacting for 2.2 hours, adding 10 wt % acetic acid to neutralize to a pH of 7, filtering, washing with water, washing with methanol, and drying at 100°C for 2.1 hours to obtain phenylsilane microspheres.
[0026] Preparation Example 2 The preparation method of phenylsilane microspheres comprises the following steps: adding emulsifier OP-10 to a sodium hydroxide solution, heating to 45°C, stirring evenly, dripping phenyltrimethoxysilane at 2.8 g / min, reacting for 2.3 hours, adding 10 wt % acetic acid to neutralize to a pH of 7, filtering, washing with water, washing with methanol, and drying at 100°C for 2.2 hours to obtain phenylsilane microspheres.
[0027] Preparation Example 3 The preparation method of phenylsilane microspheres comprises the following steps: adding emulsifier OP-10 to a sodium hydroxide solution, heating to 50°C, stirring evenly, dripping phenyltrimethoxysilane at 3.3 g / min, reacting for 2 hours, adding 10 wt% acetic acid to neutralize to a pH of 7, filtering, washing with water, washing with methanol, and drying at 105°C for 2 hours to obtain phenylsilane microspheres.
[0028] Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 1 is that the phenylsilane microspheres are further treated as follows: 5.8 g of phenylsilane microspheres are added to 50 mL of 4.7 wt % magnesium chloride alcohol aqueous solution, the alcohol-water volume ratio is 1:1, dispersant OP-10 is added, and after ultrasonic dispersion, 4 wt % sodium hydroxide alcohol aqueous solution is dripped at 55 ° C. After reacting for 18 hours, the mixture is alternately washed with water and ethanol until the pH is 7, and then dried at 100 ° C. for 6 hours.
[0029] Preparation Example 5 The difference between Preparation Example 5 and Preparation Example 1 is that the phenylsilane microspheres are further treated as follows: 6.1 g of phenylsilane microspheres are added to 45 mL of 4.86 wt% magnesium chloride alcohol aqueous solution, the volume ratio of ethanol to water is 1:1, dispersant OP-10 is added, and after ultrasonic dispersion, 4.5 wt% sodium hydroxide alcohol aqueous solution is added dropwise at 60°C, the volume of ethanol to water is 1:1, and after reacting for 19 hours, the microspheres are alternately washed with water and ethanol to a pH of 7, and then dried at 110°C for 5 hours.
[0030] Preparation Example 6 The difference between Preparation Example 6 and Preparation Example 4 is that in Preparation Example 6, the mass fraction of magnesium chloride in the alcohol aqueous solution of magnesium chloride is 2.25wt%.
[0031] Preparation Example 7 The difference between Preparation Example 7 and Preparation Example 4 is that in Preparation Example 7, the mass fraction of magnesium chloride in the alcohol aqueous solution of magnesium chloride is 6.58wt%. Preparation Examples 8-16 of Modified Graphene Oxide
[0032] Preparation Example 8 The preparation method of modified graphene oxide comprises the following steps: ultrasonically dispersing 0.3 g of graphene oxide in a mixed solution of 80 mL of ethanol and 3.5 mL of water, adding 5.9 mL of 10 wt% ammonia solution and stirring evenly, adding 3 mL of tetraethoxysilane, stirring for 24 hours, vacuum filtering, ethanol washing, suction filtering, and vacuum drying.
[0033] Preparation Example 9 The preparation method of modified graphene oxide comprises the following steps: ultrasonically dispersing 0.25 g of graphene oxide in a mixed solution of 75 mL of ethanol and 3 mL of water, adding 5.2 mL of 10 wt% ammonia solution and stirring evenly, adding 2.5 mL of tetraethoxysilane, stirring for 24 hours, vacuum filtering, ethanol washing, suction filtering, and vacuum drying.
[0034] Preparation Example 10 The preparation method of modified graphene oxide comprises the following steps: ultrasonically dispersing 0.37 g of graphene oxide in a mixed solution of 85 mL of ethanol and 3.9 mL of water, adding 6.2 mL of 10 wt% ammonia solution and stirring evenly, adding 4 mL of tetraethoxysilane, stirring for 24 hours, vacuum filtering, ethanol washing, suction filtering, and vacuum drying.
[0035] Preparation Example 11 The difference between Preparation Example 11 and Preparation Example 8 is that in Preparation Example 11, the amount of tetraethoxysilane added is 1 mL.
[0036] Preparation Example 12 The difference between Preparation Example 12 and Preparation Example 8 is that in Preparation Example 12, the amount of tetraethoxysilane added is 5.5 mL.
[0037] Preparation Example 13 The difference between Preparation Example 13 and Preparation Example 8 is that in Preparation Example 13, the modified graphene oxide is further treated as follows: 1 g of modified graphene oxide is ultrasonically dispersed in 100 mL of Tris-HCl buffer, the pH of the Tris-HCl buffer is 8.5, the concentration is 0.1 mol / L, 0.2 g of dopamine hydrochloride is added, and after magnetic stirring at room temperature for 24 hours, centrifugation, ethanol washing, and drying.
[0038] Preparation Example 14 The difference between Preparation Example 14 and Preparation Example 8 is that in Preparation Example 14, the modified graphene oxide is further treated as follows: 1.3 g of modified graphene oxide is ultrasonically dispersed in 100 mL of Tris-HCl buffer, the pH of the Tris-HCl buffer is 8.5, the concentration is 0.1 mol / L, 0.26 g of dopamine hydrochloride is added, and after magnetic stirring at room temperature for 24 hours, centrifugation, ethanol washing, and drying are performed.
[0039] Preparation Example 15 The difference between Preparation Example 15 and Preparation Example 13 is that in Preparation Example 15, the added amount of dopamine hydrochloride is 0.1 g.
[0040] Preparation Example 16 The difference between Preparation Example 16 and Preparation Example 13 is that in Preparation Example 16, the added amount of dopamine hydrochloride is 0.5 g. Example
[0041] In the embodiment of the present application, the aramid paper substrate is YT510, the one-component polyurethane adhesive is HR-729, and the release liquid is KS-776A.
[0042] Example 1 An ultra-thin aramid paper flame retardant tape, comprising an aramid paper substrate with a thickness of 0.045 mm, a flame retardant adhesive layer with a thickness of 0.025 mm, and a release layer with a thickness of 0.007 mm; The flame retardant adhesive layer includes the following raw materials in parts by weight: 48 kg of a single-component polyurethane adhesive, 12 kg of siloxane and 5 kg of a composite flame retardant, wherein the siloxane is dimethylsiloxane; the composite flame retardant includes phenylsilane microspheres, zinc borate and modified graphene oxide in a mass ratio of 1.56:0.75:1.24, wherein the phenylsilane microspheres are the phenylsilane microspheres prepared in Preparation Example 1, and the modified graphene oxide is the modified graphene oxide prepared in Preparation Example 8.
[0043] The method for preparing the ultra-thin aramid paper flame retardant tape comprises the following steps: A release liquid is coated on one side of an aramid paper substrate, and a release layer is formed after heating and drying; a single-component polyurethane adhesive, siloxane and a composite flame retardant are stirred and mixed, and coated on the side of the aramid paper substrate away from the release layer, and a flame retardant adhesive layer is formed after hot pressing and curing, and the layer is rolled up to obtain an ultra-thin aramid paper flame retardant tape.
[0044] Example 2 An ultra-thin aramid paper flame retardant tape, comprising an aramid paper substrate with a thickness of 0.03 mm, a flame retardant adhesive layer with a thickness of 0.02 mm, and a release layer with a thickness of 0.005 mm; The flame retardant adhesive layer includes the following raw materials in parts by weight: 40 kg of a single-component polyurethane adhesive, 10 kg of siloxane and 3 kg of a composite flame retardant, wherein the siloxane is dimethylsiloxane; the composite flame retardant includes phenylsilane microspheres, zinc borate and modified graphene oxide in a mass ratio of 1.25:0.68:0.98, wherein the phenylsilane microspheres are the phenylsilane microspheres prepared in Preparation Example 2, and the modified graphene oxide is the modified graphene oxide prepared in Preparation Example 9.
[0045] The method for preparing the ultra-thin aramid paper flame retardant tape comprises the following steps: A release liquid is coated on one side of an aramid paper substrate, and a release layer is formed after heating and drying; a single-component polyurethane adhesive, siloxane and a composite flame retardant are stirred and mixed, and coated on the side of the aramid paper substrate away from the release layer, and a flame retardant adhesive layer is formed after hot pressing and curing, and the layer is rolled up to obtain an ultra-thin aramid paper flame retardant tape.
[0046] Example 3 An ultra-thin aramid paper flame-retardant tape, comprising an aramid paper substrate with a thickness of 0.06 mm, a flame-retardant adhesive layer with a thickness of 0.03 mm, and a release layer with a thickness of 0.01 mm; The flame retardant adhesive layer includes the following raw materials in parts by weight: 55 kg of a single-component polyurethane adhesive, 15 kg of siloxane and 7 kg of a composite flame retardant, wherein the siloxane is dimethylsiloxane; the composite flame retardant includes phenylsilane microspheres, zinc borate and modified graphene oxide in a mass ratio of 1.67:0.89:1.32, wherein the phenylsilane microspheres are the phenylsilane microspheres prepared in Preparation Example 1, and the modified graphene oxide is the modified graphene oxide prepared in Preparation Example 8.
[0047] The method for preparing the ultra-thin aramid paper flame retardant tape comprises the following steps: A release liquid is coated on one side of an aramid paper substrate, and a release layer is formed after heating and drying; a single-component polyurethane adhesive, siloxane and a composite flame retardant are stirred and mixed, and coated on the side of the aramid paper substrate away from the release layer, and a flame retardant adhesive layer is formed after hot pressing and curing, and the layer is rolled up to obtain an ultra-thin aramid paper flame retardant tape.
[0048] Example 4 The difference between Example 4 and Example 1 is that in Example 4, the mass ratio of phenylsilane microspheres, zinc borate and modified graphene oxide is 1.25:0.25:1.98.
[0049] Example 5 The difference between Example 5 and Example 1 is that in Example 5, the mass ratio of phenylsilane microspheres, zinc borate and modified graphene oxide is 1.25:1.68:0.12.
[0050] Example 6 The difference between Example 6 and Example 1 is that in Example 6, the phenylsilane microspheres are the phenylsilane microspheres prepared in Preparation Example 4.
[0051] Example 7 The difference between Example 7 and Example 1 is that in Example 7, the phenylsilane microspheres are the phenylsilane microspheres prepared in Preparation Example 5.
[0052] Example 8 The difference between Example 8 and Example 1 is that in Example 8, the phenylsilane microspheres are the phenylsilane microspheres prepared in Preparation Example 6.
[0053] Example 9 The difference between Example 9 and Example 1 is that in Example 9, the phenylsilane microspheres are the phenylsilane microspheres prepared in Preparation Example 7.
[0054] Example 10 The difference between Example 10 and Example 1 is that in Example 10, the modified graphene oxide is the modified graphene oxide prepared in Preparation Example 11.
[0055] Embodiment 11 The difference between Example 11 and Example 1 is that in Example 11, the modified graphene oxide is the modified graphene oxide prepared in Preparation Example 12.
[0056] Example 12 The difference between Example 12 and Example 1 is that in Example 12, the modified graphene oxide is the modified graphene oxide prepared in Preparation Example 13.
[0057] Embodiment 13 The difference between Example 13 and Example 1 is that in Example 13, the modified graphene oxide is the modified graphene oxide prepared in Preparation Example 14.
[0058] Embodiment 14 The difference between Example 14 and Example 1 is that in Example 14, the modified graphene oxide is the modified graphene oxide prepared in Preparation Example 15.
[0059] Embodiment 15 The difference between Example 15 and Example 1 is that in Example 15, the modified graphene oxide is the modified graphene oxide prepared in Preparation Example 16. Comparative Example
[0060] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that no composite flame retardant is added in Comparative Example 1.
[0061] Detection Methods Ultra-thin aramid paper flame-retardant tapes were prepared according to the raw materials and preparation methods of Examples 1-15 and Comparative Example 1, and the flame-retardant tapes were subjected to flame-retardant performance tests and tensile strength tests.
[0062] Flame retardant performance test: according to GB / T 15903-1995 "Test method for flame retardancy of pressure-sensitive adhesive tapes - Suspension method", the results are recorded in Table 1; Tensile strength test: According to GB / T7753-1987 "Test method for tensile properties of pressure-sensitive adhesive tapes", cut a sample with a length of 200 mm and a width of 25 mm, stretch the sample at a speed of 300 mm / min, stretch the sample until it breaks, record the maximum tensile force, and record the results in Table 1.
[0063] Table 1 Performance test of ultra-thin aramid paper flame retardant tape project Self-extinguishing time / s Burning length / mm Tensile strength / MPa Example 1 39 121 141 Example 2 38 120 139 Example 3 38 123 140 Example 4 45 138 121 Example 5 43 141 119 Example 6 31 102 158 Example 7 32 101 160 Example 8 37 118 142 Example 9 38 120 146 Example 10 42 140 123 Embodiment 11 43 139 121 Example 12 29 103 159 Embodiment 13 30 105 162 Embodiment 14 38 115 150 Embodiment 15 39 119 147 Comparative Example 1 59 158 108 According to Examples 1-3, Comparative Example 1 and Table 1, it can be seen that the ultra-thin aramid paper flame retardant tapes prepared in Examples 1-3 have good flame retardant properties and better mechanical properties. The thickness of the aramid paper substrate is relatively thin. Adding a composite flame retardant to the flame retardant adhesive and compounding the flame retardant adhesive layer and the aramid paper substrate can effectively improve the overall strength and mechanical properties of the ultra-thin aramid paper flame retardant tape. At the same time, the flame retardant adhesive contains phenylsilane microspheres, zinc borate and modified graphene oxide. The modified graphene oxide can form a dense carbon layer. The addition of phenylsilane microspheres can improve the polyurethane adhesive layer. The amount of residual carbon can be reduced, and the stability of the carbon layer can be improved. At the same time, the phenylsilane microspheres are helpful to form more carbon layers at high temperatures, which can reduce the combustion rate and heat release rate of the material, thereby improving the thermal stability of the material. The modified graphene oxide has good insulation and flame retardant properties. The addition of phenylsilane microspheres and modified graphene oxide can not only improve the flame retardant properties of the tape, but also effectively improve the mechanical properties of the ultra-thin aramid paper flame retardant tape, so that the ultra-thin aramid paper flame retardant tape has better tensile strength. In Comparative Example 1, no composite flame retardant is added, which reduces its flame retardant and mechanical properties.
[0064] Compared with Example 1, the flame retardant properties and tensile strength of Example 4-5 are reduced. Example 4-5 changes the mass ratio of phenylsilane microspheres, zinc borate and modified graphene oxide in the composite flame retardant, indicating that there is a synergistic effect between phenylsilane microspheres, zinc borate and modified graphene oxide. The flame retardant effect can be improved by compounding according to the mass ratio in the present application. Modified graphene oxide, zinc borate and phenylsilane microspheres can jointly improve the stability of the carbon layer. At the same time, modified graphene oxide can improve the thermal conductivity and disperse the heat, so that the non-combustion part can disperse the heat and reduce the spread of flame.
[0065] Compared with Example 1, the flame retardant properties of Example 6-7 are improved. When preparing the phenylsilane microspheres used in Example 6-7, magnesium chloride and sodium hydroxide are used to perform a magnesium hydroxide precipitation coating treatment. Magnesium chloride reacts with sodium hydroxide to generate magnesium hydroxide, which is deposited on the surface of the phenylsilane microspheres. Magnesium oxide generated by thermal decomposition of magnesium hydroxide can block heat transfer and radiation, thereby improving the flame retardant properties of the phenylsilane microspheres and further improving the stability of the carbon layer.
[0066] Compared with Examples 6-7, the flame retardant properties of Example 8-9 are reduced. During the preparation of the phenylsilane microspheres used in Example 8-9, the mass fraction of magnesium chloride was changed. The mass fraction of magnesium chloride was reduced, and the content of magnesium hydroxide was reduced, which resulted in a decrease in flame retardant properties. The mass fraction of magnesium chloride was increased, and the content of magnesium hydroxide was increased. Magnesium hydroxide was unevenly deposited on the surface of the phenylsilane microspheres, which affected the flame retardant properties of the phenylsilane microspheres.
[0067] Compared with Example 1, the flame retardant performance of Example 10-11 is reduced. The modified graphene oxide used in Example 10-11 changes the amount of tetraethoxysilane added. The amount of tetraethoxysilane added is reduced, and the content of silicon dioxide deposited on the surface of the modified graphene oxide is reduced. Silicon dioxide has good flame retardant and insulating properties, which reduces the flame retardant performance of the tape. The amount of tetraethoxysilane added is increased, and the content of silicon dioxide obtained by hydrolysis is increased, and its deposition on the surface of the modified graphene oxide is uneven, which reduces the flame retardant performance of the modified graphene oxide.
[0068] Compared with Example 1, the flame retardant properties of Example 12-13 are improved. The modified graphene oxide used in Example 12-13 is surface-treated with dopamine hydrochloride. Dopamine hydrochloride can self-polymerize on the surface of the modified graphene oxide to form a polydopamine layer, which can effectively improve the dispersibility of the modified graphene oxide, thereby facilitating the improvement of the modified graphene oxide in the one-component polyurethane adhesive and improving the flame retardant properties of the flame retardant adhesive layer.
[0069] Compared with Examples 12-13, the flame retardant properties of Example 14 are reduced in Example 14-15, and the flame retardant properties of Example 15 are similar to those of Examples 12-13. The modified graphene oxide used in Examples 14-15 changes the amount of dopamine hydrochloride added. The reduced amount of dopamine hydrochloride added makes the coating of the polydopamine layer incomplete, and the effect of improving the dispersibility of the modified graphene oxide decreases. The increased amount of dopamine hydrochloride added makes the polydopamine layer thicker, but its dispersion performance is not significantly improved, and its flame retardant performance is not significantly changed compared with Examples 12-13.
[0070] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An ultra-thin aramid paper flame retardant tape, characterized in that: It includes an aramid paper substrate with a thickness of 0.03-0.06 mm, a flame retardant adhesive layer with a thickness of 0.02-0.03 mm, and a release layer with a thickness of 0.005-0.01 mm; The flame retardant adhesive layer comprises the following raw materials in parts by weight: 40-55 parts of a single-component polyurethane adhesive, 10-15 parts of siloxane and 3-7 parts of a composite flame retardant; the release layer is formed by coating a release liquid and drying it.
2. The ultra-thin aramid paper flame retardant tape according to claim 1, characterized in that: The composite flame retardant comprises phenylsilane microspheres, zinc borate and modified graphene oxide.
3. The ultra-thin aramid paper flame retardant tape according to claim 2, characterized in that: The mass ratio of phenylsilane microspheres, zinc borate and modified graphene oxide in the composite flame retardant is (1.25-1.67):(0.68-0.89):(0.98-1.32).
4. The ultra-thin aramid paper flame retardant tape according to claim 2, characterized in that: The preparation method of phenylsilane microspheres comprises the following steps: adding an emulsifier to a sodium hydroxide solution, heating to 45-50° C., stirring evenly, dripping phenyltrimethoxysilane, reacting for 2-2.3 hours, adding 10wt% acetic acid to neutralize to a pH of 7, filtering, washing with water, washing with methanol, and drying at 100-105° C. for 2-2.2 hours to obtain phenylsilane microspheres.
5. The ultra-thin aramid paper flame retardant tape according to claim 2, characterized in that: The phenylsilane microspheres are further treated as follows: the phenylsilane microspheres are added to an alcohol aqueous solution of magnesium chloride, a dispersant is added, and after being uniformly dispersed by ultrasonication, an alcohol aqueous solution of sodium hydroxide is dripped into the microspheres at 55-60° C., reacted for 18-19 hours, washed alternately with water and ethanol until the pH is 7, and then dried at 100-110° C. for 5-6 hours.
6. The ultra-thin aramid paper flame retardant tape according to claim 2, characterized in that: The preparation method of modified graphene oxide comprises the following steps: ultrasonically dispersing graphene oxide in a mixed solution of ethanol and water, adding 10wt% ammonia solution and stirring evenly, adding tetraethoxysilane, stirring for 24 hours, vacuum filtering, ethanol washing, suction filtering, and vacuum drying.
7. The ultra-thin aramid paper flame retardant tape according to claim 2, characterized in that: The modified graphene oxide is further treated as follows: the modified graphene oxide is ultrasonically dispersed in a Tris-HCl buffer, dopamine hydrochloride is added, magnetic stirring is performed at room temperature for 24 hours, and then centrifugation is performed, ethanol washing is performed, and drying is performed.
8. The method for preparing the ultra-thin aramid paper flame retardant tape according to any one of claims 1 to 7, characterized in that: The following steps are involved: A release liquid is coated on one side of an aramid paper substrate, and a release layer is formed after heating and drying; a single-component polyurethane adhesive, siloxane and a composite flame retardant are stirred and mixed, and coated on the side of the aramid paper substrate away from the release layer, and a flame retardant adhesive layer is formed after hot pressing and curing, and the layer is rolled up to obtain an ultra-thin aramid paper flame retardant tape.